Accurate diagnosis of latent tuberculosis in children, people who are immunocompromised or at risk from immunosuppression and recent arrivals from countries with a high incidence of tuberculosis : systematic review and economic evaluation /: systematic review and economic evaluation. (May 2016) - Auguste, P (Peter)
No abstract available